Efeitos do canabidiol nas memórias contextuais recompensadoras e aversivas induzidas por cocaína e cloreto de lítio. - Rayssa Briânis de Oliveira Costa (2021)
Learning to associate cues or contexts with potential rewards or threats is an adaptive process that increases an individual's survival. However, the inadequate expression of conditioned responses to rewarding or aversive stimuli may be a predisposing factor to substance abuse and anxiety disorders, respectively. Therefore, pharmacological modulation of contextual memories may be a useful approach in the treatment of certain psychiatric disorders. Considering the evidence that the endocannabinoid system modulates conditioned contextual responses, compounds that facilitate endocannabinoid signalling are potentially useful for modulating memories, both rewarding and aversive. Thus, we try to test with this work the hypothesis that cannabidiol (CBD), a phytocannabinoid present in the Cannabis sativa plant, facilitates the action of the endocannabinoid system, and can attenuate the rewarding contextual conditioning (CPP), induced by cocaine, and aversive (CPA), induced by lithium chloride (LiCl). For this, C57BL/6J mice, females, and males received injections of CBD 30 min before the phases of acquisition or expression of the mentioned behaviours (PCL and ACL). Therefore, the protocols were validated, and there was the induction of preference and aversion for PCL and ACL, respectively, at doses of 15 mg/kg of cocaine and 100 mg/kg of LiCl, through consecutive conditioning for three days. The evaluated compound, CBD at doses of 3, 10, and 30 mg/kg, was not able to inhibit the acquisition or expression of both CPP and CPA. Chemical analyses carried rule out the possibility that the CBD could have been chemically converted into another substance. As for the objective of studying the effects of CBD on conditioned aversion, there was no success in validating LiCl-induced ACL. Dose, administration time, and protocol duration adjustments may be made to establish a robust ACL protocol. Finally, the evaluation of other memory phases such as consolidation, extinction and reconsolidation, dose adjustments, administration time, and protocol duration can be performed to establish a better model and treatment proposition.